The Inhibitory Effects of Hericium erinaceus β-glucan on in vitro Starch Digestion - Ma, Bowen; Feng, Tao; Zhang, Sanfeng; Zhuang, Haining; Chen, Da; Yao, Lingyun; Zhang, Jingsong (Frontiers in Nutrition, 2021)
β-glucan has attracted extensive attention due to its health promoting effects, such as lowering the blood sugar and lipids levels, and enhancing immunity. In this study, three different β-glucans (HEBG-1, HEBG-2, HEBG-3) were obtained from Hericium erinaceus by sodium hydroxide, β-1,3-glucanase and β-1,6-glucanase, respectively. The effects of the glucans on in vitro digestion of wheat starch were investigated by Englyst method. We found that addition of HEBGs significantly reduced the digestibility of starch, showing as decreased RDS and pGI, and increased SDS and RS content. In addition, the inhibitory effects positively correlated with the molecular weight of HEBG. The triple helix structure in HEBG plays important roles in inhibiting starch digestion. And β-1,3- glucan showed stronger inhibitor effects than those of β-1,6- glucan. This study unravels the mechanism of HEBG on inhibition of starch digestion and provides a theoretical understanding for the application of edible mushroom β-glucan to the development of low glycemic index starchy foods.